2018
DOI: 10.1080/09603123.2018.1499881
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of wheat photosynthesis by fine particulate (PM2.5) pollution over the North China Plain

Abstract: The negative impact of rapid urbanization in developing countries has led to a deterioration of urban and regional air quality. Much attention has been given to the impact of fine particulate pollution on urban public health. However, very little attention has been given to its impact on the regional ecosystem such as the agricultural ecosystem. Thus, we evaluate the direct impact of air pollution on the reduction of wheat photosynthesis by fine particulate matter (PM) pollution in the world's most heavily pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 11 publications
2
23
1
Order By: Relevance
“…This result con rms our previous study (Kiyomizu et al 2019) and the study for Norway spruce in central Europe that reported decreased Δ 13 C with air pollution (Čada et al 2016), which indicates that long-term water use e ciency becomes higher as nitrogen oxides increase (Kume et al 2006). The evaluation of the effect of air pollution on long-term water use e ciency by using the leaf carbon isotope ratio (δ p ) can be di cult because of the opposite effect of fossil fuel δ 13 (δ p ) of Pinus densi ora foliage in Japanese and Korean cities, respectively. In spite of these di culties, we successfully obtained a clear trend of Δ 13 C in relation to atmospheric nitrogen oxides (Fig.…”
Section: Restrictions Of Photosynthesis By Air Pollution In the Four Urban Roadside Tree Speciessupporting
confidence: 88%
See 4 more Smart Citations
“…This result con rms our previous study (Kiyomizu et al 2019) and the study for Norway spruce in central Europe that reported decreased Δ 13 C with air pollution (Čada et al 2016), which indicates that long-term water use e ciency becomes higher as nitrogen oxides increase (Kume et al 2006). The evaluation of the effect of air pollution on long-term water use e ciency by using the leaf carbon isotope ratio (δ p ) can be di cult because of the opposite effect of fossil fuel δ 13 (δ p ) of Pinus densi ora foliage in Japanese and Korean cities, respectively. In spite of these di culties, we successfully obtained a clear trend of Δ 13 C in relation to atmospheric nitrogen oxides (Fig.…”
Section: Restrictions Of Photosynthesis By Air Pollution In the Four Urban Roadside Tree Speciessupporting
confidence: 88%
“…In spite of these di culties, we successfully obtained a clear trend of Δ 13 C in relation to atmospheric nitrogen oxides (Fig. 3) by both correction of the effect of fossil fuel δ 13 C and evaluation of relative changes in Δ 13 C (Eq. 2).…”
Section: Restrictions Of Photosynthesis By Air Pollution In the Four Urban Roadside Tree Speciesmentioning
confidence: 99%
See 3 more Smart Citations